2023
DOI: 10.1007/s10238-023-01029-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between admission systemic immune-inflammation index and mortality in critically ill patients with sepsis: a retrospective cohort study based on MIMIC-IV database

Abstract: Systemic immune-inflammation index (SII) has been identified as a prognostic biomarker for various diseases. Our study aimed to investigate the association between SII and mortality risk in critically ill patients with sepsis, thus exploring possible tools for rapid screening. This retrospective cohort study was conducted using clinical data extracted from the Medical Information Mart for Intensive Care Database. The study included only patients diagnosed with sepsis admitted to the intensive care unit for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Our study found that the higher SII groups (Q3 and Q4) had higher 28-day mortality in patients with SA-AKI. The 28-day mortality rate in the low SII group (Q1) was higher compared to the Q2 group, but the difference was not significant, consistent with previous findings in critically ill patients [24]. The literature contains little information on the relationship between the SII and short-term mortality in SA-AKI [25].…”
Section: Discussionsupporting
confidence: 79%
“…Our study found that the higher SII groups (Q3 and Q4) had higher 28-day mortality in patients with SA-AKI. The 28-day mortality rate in the low SII group (Q1) was higher compared to the Q2 group, but the difference was not significant, consistent with previous findings in critically ill patients [24]. The literature contains little information on the relationship between the SII and short-term mortality in SA-AKI [25].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the lowest risk of 28-day mortality was at the SII levels of 774.46 × 10 9 /L. [ 112 ]…”
Section: Systemic Immune-inflammation Indexmentioning
confidence: 86%
“… 21 , 33 However, a retrospective study showed that not only is a higher SII associated with the death of critically ill patients with sepsis, but a lower SII also led to an increased risk of short‐term death. 22 Low SII levels theoretically signal that the body may be suffering from significant inflammation and immune suppression disorder. However, intestinal obstruction patients who are about to undergo surgical treatment rarely experience these conditions before surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Meanwhile, a retrospective study showed that SII was associated with short‐term mortality in the population of critically ill patients with sepsis. 22 However, there have been limited studies on the inflammatory factors in patients with intestinal obstruction who are at a high risk of developing postoperative sepsis. We speculated that SII is a risk factor for sepsis after intestinal obstruction surgery.…”
Section: Introductionmentioning
confidence: 99%